2024
DOI: 10.3390/cryst14020120
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of Yb: CALYGLO Crystal for Ultrashort Pulse Laser Applications

Zebin Wang,
Jian Liu,
Peng Chen
et al.

Abstract: Yb:CALYGLO crystals with a dopant concentration of 5 at.% were successfully grown using the Czochralski method. The crystal samples were extensively studied to analyze their structure, room temperature and low temperature spectra, and laser properties. The highest absorption cross-section at 977 nm was calculated to be 1.83 × 10−20 cm2 for σ polarization and 5.32 × 10−20 cm2 for π polarization. Similarly, the emission cross-section was determined to be 1.38 × 10−20 cm2 at 980 nm for σ polarization and 2.28 × 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Ultrafast and tunable lasers show extensive applications in intelligent processing [1], communication and remote sensing [2], national defense and military [3], medical beauty, and scientific research [4] because of the high pulse energy, high peak power, and short duration. In recent years, crystals with disordered structures have attracted extensive attention for ultrafast and tunable lasers gain media due to the wide emission band [5][6][7][8]. The random distribution of cations with different valences in the same lattice position leads to the disordered distribution of the lattice field, which leads to the uneven broadening of absorption and emission spectra [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrafast and tunable lasers show extensive applications in intelligent processing [1], communication and remote sensing [2], national defense and military [3], medical beauty, and scientific research [4] because of the high pulse energy, high peak power, and short duration. In recent years, crystals with disordered structures have attracted extensive attention for ultrafast and tunable lasers gain media due to the wide emission band [5][6][7][8]. The random distribution of cations with different valences in the same lattice position leads to the disordered distribution of the lattice field, which leads to the uneven broadening of absorption and emission spectra [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The ABCO 4 family crystallizes in the K 2 NiF 4 tetragonal structure with a space group of I 4 /mmm, has a complex and disordered lattice field, which causes a large inhomogeneous broadening of absorption and emission spectra. In general, rare-earth-doped CaYAlO 4 , CaGdAlO 4 , and SrLaAlO 4 laser crystals have been widely studied in ultrafast and tunable laser fields [7,9,15,[21][22][23][24]. In 2016, Liu et al reported a stable 458 femtosecond continuouswave mode-locked pulse in the Nd:SrLaAlO 4 crystal at 1077.9 nm with an average power output of 520 mW [21].…”
Section: Introductionmentioning
confidence: 99%